Nature’s Song under the Bombs: Pastoral Echoes in some Scottish War Poems - Stéphanie NOIRARD (E-REA)
Scotland has a great tradition of nature writing, but by the end of the 19th century, glens, bens, lochs, bracken and quiet clachans seemed to have become the essential props of any would-be Scottish author, solidly rooted in his homeland, as part of a made-up romanticized tradition. Since the First World War, however, many authors have been rejecting or trying to build the tradition anew. After a rapid overview of Gaelic, Scots and English nature writing, this article explores the particular roles of this tradition in World War I and World War II poetry, both in terms of theme and structure, focusing particularly on aural elements. It first shows the slow degradation of nature’s sounds in the poems on the First World War – from nostalgic reminiscences, comforting memories or patriotic pleas to human cries in the din of guns. It then focuses on anti-pastoral and the impact the idea of a waste-land had on World War II poetry, considering how the sounds of nature can still be heard in a ruined world of bombed cities and human atrocities. A last part is dedicated to the new poetic forms authors try to create in order to struggle against silence and destruction, as well as to pastoral as a subversive form and the use of sonic “carnivalesque” and resistance.